(3CgHI GdeYGO aj GdeHOC hGdeYGOs - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj Od Ydi eYQaI PGJg HbOQJg (B... (3aCeG GdcdGe Ydi GdebOeI afbhd hbHd GdNhV ajeG hUafG GdcJGH dCLdg dHO ef PcQ GdGSJOdGd Ydi KHhJ chfg JYGdi YGOdG aj Mcegs
(3BNQgG (B:s
(3BNQgG(B: (3ajTcd GdebJVi Yf dRhe GdJHOd hGdcPH Gddge EdG Cf jMed BjGJ GdhYjO Ydi GSJMbGb eG ChYO Hg dG Ydi hbhYg HGdaYd haj GdBjI GdePchQI GTGQI Edi Pdc MjK bGd(B: (3aLRGFg Lgfe NGdkOG ajgG(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3GdPQjYI, L (B2: 269s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds